Relationship between Mental Health and Burnout in Al-E-Jalil Hospital`s Staff, 2014 - Akram Sanagoo; Naser Behnampour; Ahmad Taghavee; Fariba Baiky (Golestan University of Medical Sciences, 2015)
Background and Objective: Mental health is one of essential needs that has a critical role in sustainable development.  Burnout , a physical and mental fatigue and a sense of reduced capabilities, is a leading factor in lowering mental health efficiency .this study aimed at determining the relationship between burnout and mental health in  Al -E-Jalil hospital`s staff. Material and Methods: This descriptive - analytical research was conducted on 179 Al-E-Jalil hospital`s staff recruited via Census method in 2014. The data was collected by mental health questionnaire (G.H.Q-28) and Burnout (Maslach) questionnaires, and analyzed by kruskal Wallis, Mann-Whitney and Spearman correlation. Results: Significant relationship between mental health and burnout (P=0.0001, r=-0.844) showed that mental health enhancement  reduced the level of  burn out. The mean mental health (19.28± 10.77)  was excellent . Two domains of "somatization" and "depression and suicidal tendencies" were better than "social dysfunction" and "anxiety and sleep disorders". The highest mean was related to  "Depersonalization" and "emotional exhaustion"  and the lowest one to " personal accomplishment". Conclusion: The findings show that there is  a negative significant relationship between mental health and burnout that means by enhancing mental health the staff experiences lower level of  burn out.